2019
DOI: 10.1038/s41418-018-0260-y
|View full text |Cite
|
Sign up to set email alerts
|

Accurate elimination of superfluous attachment cells is critical for the construction of functional multicellular proprioceptors in Drosophila

Abstract: Here, we show for the first time that developmental cell death plays a critical role in the morphogenesis of multicellular proprioceptors in Drosophila. The most prominent multicellular proprioceptive organ in the fly larva, the pentascolopidial (LCh5) organ, consists of a cluster of five stretch-responsive sensory organs that are anchored to the cuticle via specialized attachment cells. Stable attachment of the organ to the cuticle is critical for its ability to perceive mechanical stimuli arising from muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Mitochondrial biogenesis can generate new functional mitochondria to increase the number of mitochondria through transcriptional regulation [ 22 ], and inhibition of mitochondrial biogenesis can inhibit tumor cell proliferation [ 23 ]. Mitophagy is a form of autophagy by which the damaged or superfluous mitochondria are phagocytosed and degraded [ 24 26 ], and inhibition of mitophagy can aggravate mitochondrial damage and promote mitochondria-mediated apoptosis [ 27 , 28 ]. Because mitochondria play a key role in cell proliferation and death, many studies have demonstrated that targeting mitochondria can inhibit tumor growth or induce apoptosis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial biogenesis can generate new functional mitochondria to increase the number of mitochondria through transcriptional regulation [ 22 ], and inhibition of mitochondrial biogenesis can inhibit tumor cell proliferation [ 23 ]. Mitophagy is a form of autophagy by which the damaged or superfluous mitochondria are phagocytosed and degraded [ 24 26 ], and inhibition of mitophagy can aggravate mitochondrial damage and promote mitochondria-mediated apoptosis [ 27 , 28 ]. Because mitochondria play a key role in cell proliferation and death, many studies have demonstrated that targeting mitochondria can inhibit tumor growth or induce apoptosis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the five scolopidia originates in a single precursor cell that divides asymmetrically to generate five of the six cell types that construct the mature organ: the neuron, scolopale, ligament, cap, and cap-attachment cell ( Brewster and Bodmer, 1995 ; Figure 1A–C ). Three of the five cap-attachment cells are rapidly removed by apoptosis, leaving two cap-attachment cells that anchor the five cap cells to the epidermis ( Avetisyan and Salzberg, 2019 ). Later in development, following the migration of the LCh5 organ from the dorsal to the lateral region of the segment, a single ligament-attachment cell is recruited from the epidermis to anchor the five ligament cells to the cuticle ( Inbal et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the five scolopidia originates in a single precursor cell that divides asymmetrically to generate five of the six cell types that construct the mature organ: the neuron, scolopale, ligament, cap and cap-attachment cell (Brewster and Bodmer, 1995)(Figure 1A-C). Three of the five cap-attachment cells are rapidly removed by apoptosis, leaving two cap-attachment cells that anchor the five cap cells to the epidermis (Avetisyan and Salzberg, 2019). Later in development, following the migration of the LCh5 organ from the dorsal to the lateral region of the segment, a single ligament-attachment cell is recruited from the epidermis to anchor the five ligament cells to the cuticle (Inbal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%